Biofilm formation analysis and molecular identification of copper-resistant bacteria isolated from PT Freeport Indonesia’s tailings - Maria Massora; Erni Martani; Eko Sugiharto; Roberth Sarwom; Tumpal Sinaga (Indonesian Journal of Biotechnology, 2017)
Copper is an essential macronutrient for living organisms. Nevertheless, at high concentrations, it is toxic to most forms of life, including microorganisms. In this research, we examined the biofilm formation ability and identified the molecular characteristics of copper-resistant bacteria isolated from PT Freeport Indonesia’s tailings. Four bacteria isolates from PT Freeport Indonesia’s tailings were used in this study. Qualitative analysis of biofilm formation by copper-resistant bacteria was performed using the Scanning Electron Microscopy (SEM) method and Microtiter Plate Biofilm Assay. The results showed that the C53 isolate could be categorized as a strong biofilm former, and three other isolates (C38, C40, and C43) as medium biofilm formers. The identity of the selected isolates was based on 16S rRNA gene sequence analysis: C38 isolate had a 99% similarity to Bacillus cereus strain HM85, C43 isolate had a 99% similarity to Bacillus subtilis strain EN16, C40 isolate had a 99% similarity to Lycinibacillus fusiformis strain MB52, and C53 isolate had a 98% similarity to Pseudomonas aeuruginosa strain GGRJ21. The capability of the C53 isolate to form strong biofilm can be exploited in bioremediation processes aiming to remove copper from tailings.